PENEGAKAN HUKUM TERHADAP PERDAGANGAN ORANG DALAM (INSIDER TRADING) DI PASAR MODAL INDONESIA - , David Ronald, SE, DR. Sulistiowati, SH.,M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This Thesis examines the law enforcement of Insider Trading in Indonesian Capital Market. The purpose of the study is to discover the constraints faced by Bapepam-LK in terms of supervision and verification of Insider trading in Indonesia, and efforts that can be taken to solve the constraints problem. This research is a descriptive study with normative-empirical method. The data from this study was obtained from library research to obtain secondary data, and also by field research in form of interview to complete the data. Library research conducted by comparison between Indonesian and United States of America capital marketâs law. This research discovered that the constraints of insider trading law enforcement in Indonesia such as, the measurement of materiality fact, misappropriation theory, rule of insider restrictions to perform transaction, business judgment rule theory, and law evidence. Efforts that can be taken by Bapepam-LK such as, misappropriation theory, short-swing liability, the legal shifting burden of proof, adapting the supervision and investigation technique such as, surveillance and bounties.